2018
DOI: 10.3390/ijms19113461
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Cellular Mechanical Behavior Adaptation to Substrate Mechanics Identified by Atomic Force Microscope

Abstract: Cell–substrate interaction plays an important role in intracellular behavior and function. Adherent cell mechanics is directly regulated by the substrate mechanics. However, previous studies on the effect of substrate mechanics only focused on the stiffness relation between the substrate and the cells, and how the substrate stiffness affects the time-scale and length-scale of the cell mechanics has not yet been studied. The absence of this information directly limits the in-depth understanding of the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…During the indenting process, the used AFM probe was spherical and its indenting speed at 20 µm/s was significantly faster than the intracellular fluid efflux rate [28]. Therefore, the measured cell can be treated as incompressible.…”
Section: Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…During the indenting process, the used AFM probe was spherical and its indenting speed at 20 µm/s was significantly faster than the intracellular fluid efflux rate [28]. Therefore, the measured cell can be treated as incompressible.…”
Section: Elasticitymentioning
confidence: 99%
“…Therefore, the probe-cell interaction could be treated as a poroelastic half-space indented by a sphere indenter during the force-relaxation process. The diffusion coefficient, D, was quantified using the empirical mathematical model as follows [28,29],…”
Section: Poroelasticitymentioning
confidence: 99%
“…Moreover, the changes of F-actin orientation and quantity due to different latrunculin B treatment dosages are clearly shown in the F-actin fluorescence images. Therefore, it is clear that the proposed IRAQ is quite sensitive to detecting the F-actin cytoskeleton change, and the comparison indicated that IRAQ can be reliably used in further research to study the quantitative relation between the actin cytoskeleton morphology and the cellular mechanical properties, as previous studies have shown that latrunculin B treatment tends to alter the cell mechanical properties significantly [9][10][11][12].…”
Section: Quantification Results Comparisonmentioning
confidence: 99%
“…As one of the three main components of the cellular cytoskeleton, the actin cytoskeleton (i.e., actin filaments) controls cell mechanotransduction dynamics through directly affecting the motility, contractility, and mechanical stability of the cells [2,6,8]. Specifically, the actin cytoskeleton responds to the external stimuli, such as the change of the substrate stiffness and external forces, applied on the cells through polymerization or depolymerization in order to regulate cellular physiological properties [9][10][11][12]. Therefore, the morphology of the actin cytoskeleton is of great importance in understanding the cellular dynamic mechanotransduction responses.…”
Section: Introductionmentioning
confidence: 99%
“…Using AFM electronic feedback loops allows the recording of nanoscale force indentations of the cell surface as a function of the applied constant mechanical force. For example, this type of approach has been applied to investigate the biological behavior and function of living cells in response to external mechanical force …”
Section: Summary Of Frap Fitting Parameters In Living Hela Cells Sinmentioning
confidence: 99%